Comparative Study of Crude and Wine-Processing Corni Fructus on Chemical Composition and Antidiabetic Effects. (2nd December 2019) - Bi, Huailong; Niu, Dou; Guo, Chen; Li, Jia; Chen, Xue; Zhang, Yuan; Wang, Shaojun; Bai, Jiqing; Li, Xing; Kang, Jiefang
Abstract : Wine processing is a specialized technology which involves sautéing crude herbal medicine using Chinese rice wine. Herein, we identified the changes in chemical profiles and antidiabetic effects of Corni Fructus (CF) after wine processing in high-fat diet (HFD) streptozotocin- (STZ-) induced diabetic mice. A novel high-efficiency method for simultaneously quantifying gallic acid, 5-hydroxymethylfurfural, morroniside, loganin, sweroside, and cornuside by UPLC was developed, and validating crude and wine-processing CF was done for the first time. Mice were randomly divided into the following groups and orally given different solutions for 4 weeks: normal group (NC, 0.4% (w/v) CMC-Na), model group (DM, 0.4% (w/v) CMC-Na), crude CF group (CP, 3.87 g/kg), and wine-processing CF group (PP, 3.87 g/kg) followed by HFD and multiple subcutaneous injection of STZ (40 mg/kg) to induce the diabetes model except the NC group. Biochemical indexes (body weight, fasting blood glucose level, lipid level, insulin, and free fatty acid) and other parameters involving liver toxicity were measured with commercial kits and immunohistochemical method. Comparative studies on pharmacology showed that the crude extracts possess higher efficacy on hypoglycemia and hypolipidemia, while wine-processing products exhibit better effects on liver preservation. Our data suggested that wine processing was recommended when CF was used for protecting the liver; however, crude products should be used as antidiabetic drugs.